Novel approaches for stability improvement in natural medicines - Thakur, Lovely; Ghodasra, Umang; Patel, Nilesh; Dabhi, Mahesh (Pharmacognosy Reviews)
Natural product market has seen tremendous growth in the last few years. It results in the formulation of a number of proprietary herbal products, majority of them being multi-component formulations. With the advancement of herbal drug treatments, it has now been observed that many of the constituents present in the drug may react with each other, raising the serious concern about the stability of such formulations which is an important issue in the field of phytochemistry and natural medicines. Natural products are often prone to deterioration, especially during storage, leading to loss of active component, production of metabolites with no activity and, in extreme cases, production of toxic metabolites. This area needs to be addressed in order to determine the efficacy of the formulation. Understanding the problems related to natural product stability can give the idea of dealing with the stability issues. Modifications of the conventional herbal formulations can deal with the stability problems to a large extent. This article deals with the stability problems and is aimed to provide some tools and techniques to increase stability of natural medicines and herbal formulations.
Keywords: Herbal formulation; instability; natural products; phytoformulations; shelf-life; stability